The effect of high impact crossfit exercises on stress urinary incontinence in physically active women. Issue 2 (8th January 2019) - Yang, Jean; Cheng, Julie W.; Wagner, Hillary; Lohman, Everett; Yang, Sang H.; Krishingner, Gene Austin; Trofimova, Alexandra; Alsyouf, Muhannad; Staack, Andrea
Abstract : Aims: The impact of CrossFit (high energy and intensity exercise) on SUI has not been well described. This study evaluates the incidence of SUI in physically active women, and examines specific exercises that can increase SUI. Methods: A cross‐sectional study was conducted in women from four CrossFit centers and one aerobic center for comparison. Participants were surveyed regarding baseline demographics, activity levels, severity, and frequency of leakage during CrossFit exercises as well as preventative strategies against SUI. Participants were stratified based on age, body mass index, types of exercises, parity, delivery, and compared using Mann Whitney‐U and Chi square. Results: This study had 105 CrossFit (mean = 36.9 years) and 44 aerobic (mean = 29.0 years) participants. Fifty women reported SUI during exercises, while none of the aerobic women reported SUI during exercise. The top three CrossFit exercises associated to SUI were double‐unders (47.7%), jumping rope (41.3%), and box jumps (28.4%). CrossFit women with a history of parity had significantly more episodes of SUI with box jumps, jumping rope, double‐unders, thrusters, squats without weights, squats with weights, and trampoline jumping ( P  < 0.001). The top preventative strategies were emptying the bladder before workouts, wearing dark pants, and performing Kegel exercises during workout. Vaginal delivery (OR 4.94) and total incontinence symptom severity index (OR 1.45) were both significant predictors of SUI during exercise ( P  < 0.05). Conclusion: There is a significantly higher risk of SUI during CrossFit exercises associated with previous pregnancy and vaginal delivery but also in nulliparous women. In general, women participating in CrossFit have been applying preventative measures for protection of SUI during exercises.